Implementasi Kebijakan Retribusi Izin Minuman Beralkohol - Hubertus (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2023)
The purpose of this study is to determine the Implementation of Alcoholic Beverage License Levy Policy in Merauke Regency. The type of research used is qualitative research with a descriptive approach and uses the basis of field research research. The determination of informants is carried out in a purposive way with a total of 6 informants. The results of this study show that the implementation of the Alcoholic Beverage License Levy Policy in Merauke Regency has not been implemented optimally, it can be seen from several indicators; First; Policy Standards and Objectives, namely the target of the policy to monitor the circulation of alcoholic beverages in Merauke district. Second; Resources, namely people registered with the One-Stop Integrated Services Investment Office, are obedient to pay the levy. Third; The characteristics of the Implementing Organization, namely sanctions given to people who disobey to pay retribution, the sanctions given are early reprimands even to the point of severe sanctions in the form of revocation of business licenses. Fourth; Communication between organizations, namely about the establishment of cooperation between stakeholders involved in licensing issues and control of alcoholic beverages. Fifth; The disposition or attitude of the Implementers, namely the socialization related to the licensing of alcoholic beverage businesses. Sixth; The Socio-Economic Environment, Poitik, namely the alcoholic beverage permit, has a negative impact on the community because it triggers crime, so there needs to be special policies in efforts to circulate alcoholic beverages, as well as more targeted and effective enforcement of legal sanctions.